2009
DOI: 10.1111/j.1747-0803.2009.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adult Congenital Heart Disease by Cardiac Magnetic Resonance Imaging

Abstract: Cardiovascular magnetic resonance (CMR) imaging plays an essential role in the evaluation and follow-up of adult congenital heart disease (ACHD), providing safe, high-resolution imaging of some of the most complex anatomies encountered. Unlimited by acoustic windows and capable of tissue characterization, CMR is devoid of ionizing radiation and provides superior three-dimensional spatial resolution to transthoracic echocardiography and superior temporal resolution to computed tomography, making it the gold sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Sagittal images seemed better for assessing the infundibulum and the pattern of attachment of the anterior leaflet. Small septal defects are difficult to reliably identify with cardiac MRI, given the decreased temporal resolution of the technique compared with traditional echocardiographic imaging [37]; this was also shown in our series. However, techniques for quantifying blood flow allow reliable estimation of shunt hemodynamics, which are important markers of the clinical significance of such lesions.…”
Section: Importance Of Mri In Easupporting
confidence: 59%
See 1 more Smart Citation
“…Sagittal images seemed better for assessing the infundibulum and the pattern of attachment of the anterior leaflet. Small septal defects are difficult to reliably identify with cardiac MRI, given the decreased temporal resolution of the technique compared with traditional echocardiographic imaging [37]; this was also shown in our series. However, techniques for quantifying blood flow allow reliable estimation of shunt hemodynamics, which are important markers of the clinical significance of such lesions.…”
Section: Importance Of Mri In Easupporting
confidence: 59%
“…However, visibility of the posterior leaflet is increased and tricuspid regurgitation can be quantified by cardiac MRI [37]. Radial cine images along the axis of the RV allow visualization of the function and tethering of the anterior, posterior, and septal leaflets.…”
Section: Importance Of Mri In Eamentioning
confidence: 99%
“…This modality is not restricted by body size or poor acoustic windows and is versatile, offering a repertoire of velocity-mapping and tissue-contrast options, without any ionising radiation [11,12]. The versatility presents challenges, however, and consistency of methods between studies or between centres should not be assumed.…”
Section: Cardiovascular Mrimentioning
confidence: 99%
“…Adequate baffle visualization is important as studies have shown an incidence of baffle obstruction diagnosed by TTE alone to be 11.2% in Senning (n = 89) and 31% in Mustard (n = 29) patients 21 . When it occurs, baffle stenosis is most commonly located at the distal aspect of the SVC 8 …”
Section: Discussionmentioning
confidence: 99%